The interaction of explicit and implicit contracts: A signaling approach - Marc Gürtler; Oliver Gürtler (Technische Universität Braunschweig, Institut für Finanzwirtschaft, 2012)
We analyze the interaction of explicit and implicit contracts in a model with selfish and fair principals. Fair principals are willing to honor implicit agreements, whereas selfish principals are not. Principals are privately informed about their types. We investigate a separating equilibrium in which principals reveal their type through the contract o er to the agent. If this equilibrium is played, explicit and implicit contracts are substitutes. Since the agent learns the principal's type, a selfish principal has to rely on explicit incentives. A fair principal, by contrast, can effectively induce implicit incentives and hence does not need to use explicit incentives. Interestingly, if a selfish principal can rely on more effective explicit incentives, a fair principal becomes more likely to be able to separate from the selfish type and, hence, to make better use of implicit incentives. In this sense, there is a strategic complementarity between explicit and implicit incentives.
Keywords: D82; D86; M52; 330; explicit contracts; implicit contracts; separating equilibrium; substitutes; strategic; complementarity